Linearity aspects of the ensemble of data assimilations technique. (19th June 2014) - Megner, L.; Tan, D. G. H.; Körnich, H.; Isaksen, L.; Horányi, A.; Stoffelen, A.; Marseille, G.‐J.
Abstract We examine the linearity of the Ensemble of Data Assimilations (EDA) technique with respect to the amplitude of the applied observation perturbations. We provide explicit examples to assess the linear relationship between such modifications of the observing system and the resulting changes in the EDA ensemble spread. The results demonstrate that, for a state‐of‐the‐art numerical weather prediction (NWP) system, such linearity between the applied observation perturbations and the EDA ensemble spread holds well for temporal and spatial regimes relevant to global medium‐range weather prediction: specifically, for forecast lead‐times of up to approximately 5 days, in the vertical throughout the troposphere up to the lower and middle stratosphere and for broad horizontal scales.